Exploring the Impact of Surgical Techniques on Postoperative Corneal Astigmatism: A Comparative Study between Phacoemulsification and Small Incision Cataract Surgery - Faiza Hassan; Asima Irshad; Akram, Syed Nishat; Qurat-ul-Ain Khan; Taimur Khan (Medical Journal of South Punjab, 2024)
Objective: To compare the post-surgical corneal astigmatism after phacoemulsification and small incision cataract surgery (SICS) on the basis of incision length.Methods: 140 participants, aged between 45-70 years, were divided into two groups, each having 70 patients undergoing cataract surgery by phacoemulsification and small incision. This was a randomized control trial designed to assess the outcomes of different incision lengths. The 70 patients in each group were further divided into two groups, with Group A including 35 patients based on an incision length of 1.75mm and Group B including 35 patients based on an incision length of 2.75mm during cataract surgery. All patients were thoroughly examined before surgery and after surgery on the first day, week, and sixth week.Results: Mean age of participants was 1.41± 0.494 years. With little complications, both surgical procedures produced outstanding visual results. In patients who had phacoemulsification, the initial visual recovery at the sixth postoperative week was better. Phacoemulsification's MAE for astigmatism was 0.18 ± 0.914 D and for SICS was 0.136 ± 0.962 D. The initial difference with 1.75mm incision showed that there was no significant difference (P=0.172) and with 2.75mm showed phacoemulsification gave better cylindrical output (P=0.007). Conclusion: Both the techniques, phacoemulsification and manual small incision cataract surgery (SICS) have demonstrated their efficacy in achieving excellent visual outcomes for cataract surgery. Phacoemulsification offers the advantage of early visual rehabilitation due to its smaller incision size